2019
DOI: 10.1016/j.celrep.2019.10.117
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative In Vivo Proteomics of Metformin Response in Liver Reveals AMPK-Dependent and -Independent Signaling Networks

Abstract: Highlights d Using 14-3-3 as an affinity tool reveals acute metformininduced signaling in liver d Roughly 40% of proteins induced to bind 14-3-3 by metformin require LKB1 d Metformin activates kinases PKD and MK2, independent of LKB1/AMPK d AMPK regulates store-operated calcium entry via STIM1/ STIM2 phosphorylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 108 publications
1
31
1
Order By: Relevance
“…We can exclude a role for AMPK activation in the G6P-lowering mechanism because metformin was equally effective in AMPK-KO hepatocytes. However, we cannot exclude involvement of other stress kinases like PKD and MK2 that may be activated through LKB1-independent mechanisms at high metformin (67). In this study, high substrate challenge showed trends of lower AMPK phosphorylation basally and with low metformin (0.2 mM) but enhanced AMPK phosphorylation with high metformin (0.5 mM), indicating that raised hexose phosphates do not antagonize AMPK activation by the canonical pathway.…”
Section: Metformin Lowers Glucose 6-phosphate In Hepatocytescontrasting
confidence: 57%
“…We can exclude a role for AMPK activation in the G6P-lowering mechanism because metformin was equally effective in AMPK-KO hepatocytes. However, we cannot exclude involvement of other stress kinases like PKD and MK2 that may be activated through LKB1-independent mechanisms at high metformin (67). In this study, high substrate challenge showed trends of lower AMPK phosphorylation basally and with low metformin (0.2 mM) but enhanced AMPK phosphorylation with high metformin (0.5 mM), indicating that raised hexose phosphates do not antagonize AMPK activation by the canonical pathway.…”
Section: Metformin Lowers Glucose 6-phosphate In Hepatocytescontrasting
confidence: 57%
“…This indicates the ER as a potential base for alternative activation of AMPK by CAMKK2 through effects on calcium levels. In line with this, multiple studies have now demonstrated a relationship between AMPK and the ER-localized protein stromal interaction molecule 2 (STIM2) (Chauhan et al, 2019;Nelson et al, 2019;Stein et al, 2019). From these studies STIM2 appears to complex with AMPK and CAMKK2 at the ER.…”
Section: Linking Diverse Activating Inputs Of Ampk At the Ermentioning
confidence: 74%
“…In the rest part of this study, we further investigated the potential molecular mechanism of C-176 in mediating anti-inflammatory effects under SAH condition. AMP-activated protein kinase (AMPK) is a heterotrimeric protein that functions as a key energy sensor and plays an important role in maintaining metabolism homeostasis by upregulating lipid oxidation and mitochondrial biogenesis [57]. In addition, AMPK has also been identified to be an important regulator of autophagy through upregulating the activity of Unc-51-like autophagy-activating kinase 1 (ULK1) [58].…”
Section: Discussionmentioning
confidence: 99%